PENGARUH NPF & BIAYA OPERSIONAL PER- PENDAPATAN OPERASIONAL TERHADAP FDR DAN DAMPAKNYA PADA PROFITABILITAS PERBANKAN SYARIAH - fasya fasya (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2017)
This research aimed to examine the effect of Non Performing Financing (NPF) and Operating Expenses Operating Income to Financing to Deposit Ratio (FDR), and their impact on profitability is expressed by Return on Assets (ROA) at the Indonesian Islamic Banks in the period 2013-2015. The data used in this research was obtained from the data bank's annual Condensed Financial Statement Sharia period 2013-2015. The population in this research is the whole Islamic Banks in Indonesia. The analysis technique used in this research is path analysis (path analysis) with the 8.8 version of the application lisrel student who aims to obtain a comprehensive picture of the relationship between variables. The results showed that the NPF a significant negative effect on the FDR Islamic Banks. BOPO a significant negative effect on the FDR Islamic Banks, FDR positive and significant impact on ROA Islamic Banks. While the NPF and ROA variables simultaneously affect 76% to FDR while the rest influenced by other variables. Variable NPF, ROA and FDR simultaneously influence on ROA of 70% while the rest influenced by other variables with normal value Weighted Least Squares Theory Chi-Square = 0.00 (P = 1.00).